Reading Luke in impoverished communities : a social-scientific and feminist hermeneutical approach to Luke 1:39-56 and 4:16-30 - Petersen, Darian Marlo (Stellenbosch : Stellenbosch University, 2013)
Thesis (MTh)--Stellenbosch University, 2013.